(untitled) (Research, Society and Development, 2023)
Digital Elevation Models (DEMs) are mathematical models that reproduce a topographic surface from Cartesian coordinates “x and y”, with altimetric attributes “z”, where “z” represents the variation of a surface. The MDEs have several applications, they can be used in the management of water and environmental resources. In this context, the objective of this work was to compare different sensor systems, SRTM (1, 2 and 3), COPERNICUS DEM, TopoData, ASTER GLOBAL DEM 2 and ALOS PALSAR, through a binomial system formed by the altimetric variables, verifying the dispersion and precision through the MDE data, also through the physical analysis of the altimetric profile resulting from the longest thalweg in the municipality of São Carlos. The analysis also consisted of the statistical evaluation of the MDE with Student’s T Test and Analysis of Variance (ANOVA). Continuing with the Slope Orientation Maps, verifying which were the predominant slopes, by the Altimetric Profiles of the MDEs showing small differences in elevation and, according to the analyzed pair, positional differences. The best correlation occurred between the SRTM sensors, while the worst was given by the TANDEM/TERRASAR-X family sensors. As for the physical (visual) and statistical comparisons of the MDE data, the pertinence is affirmed regarding the similarity of the SRTM 30, TopoData and NASADEM sensors, the greatest difference between ASTER GDEM and TANDEM/TERRASAR-X. The difference is due to the MDE constitution process, mainly due to the spatial resolution of each.